Testosterone Replacement Therapy and the Risk of Hypoglycemia - Analía Verónica Yamaguchi; Pablo René Costanzo; Verónica Andrea Peuchot; Pablo Knoblovits (Case Reports in Endocrinology)
We report the case of a 45-year-old man with a history of Klinefelter syndrome undergoing testosterone replacement therapy, and with type 2 diabetes treated with metformin with poor metabolic control. When vildagliptin was added to his treatment, he presented hypoglycemia after the testosterone injection. We highlight this not widely reported drug interaction between hypoglycemic agents and testosterone.